Accuracy of diagnostic tests for perilymphatic fistula: protocol for a systematic review - Situkho, Maksym; Ikezono, Tetsuo; Myhrum, Marte; Rødvik, Arne Kirkhorn; Maeda, Yukihide; Matsuda, Han; Sawada, Masafumi; Jablonski, Greg Eigner (Frontiers in Neurology, 2024)
Perilymphatic fistula (PLF) is a challenging inner ear condition, characterized by the abnormal connection between inner and middle ear and subsequent leakage of inner ear liquid (perilymph) into the middle ear. Early surgical intervention for PLF might lead to favorable audiological and vestibular outcomes. The conventional reference standard of PLF detection is the intraoperative visualization of perilymph leakage during explorative tympanotomy or endoscopic inspection; the specificity and sensitivity of this method is unknown. Systematic reviews assessing the accuracy of diagnostic tests for PLF are not available.ObjectiveTo systematically review the literature for qualitative evidence exploring the diagnostic tests for the PLF diagnosis. The proposed systematic review will answer the following question: What is the accuracy of diagnostic tests in detecting perilymphatic fistula in humans?MethodsEligibility criteria: original peer-reviewed articles regarding studies on humans of any age containing data with diagnostic test accuracy estimation (sensitivity and specificity) for PLF diagnosis or in which diagnostic test accuracy could be calculated based on data provided, without language, study design or study date limits. MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials, Scopus, and Web of Science will be searched for eligible articles. Additional manual searches will be performed. Covidence software will be used for title and abstract screening, full text review and data extraction. The risk of bias assessment will be conducted using the Quality Assessment of Diagnostic Test Accuracy 2 (QUADAS-2) tool. If two or more high-quality articles evaluating the same diagnostic test will be identified, their findings will be quantitatively synthesized; if a quantitative synthesis is not feasible, the results will be described in a narrative summary. Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) framework will be used to evaluate evidence strength. Study funded by Oslo University Hospital.